Kultura korporacji a lokalność systemu ocen w spółce-córce - Ławrynowicz, Maciej; Szambelańczyk, Jan (Corporate culture and employee performance appraisal system of daughter company, 2006)
This article examines a common problem of change in corporate culture and influence on HRM system on the local level of management. Research recognizes some errors in goal setting that may frequently disturb the process of performance appraisal system. Our focus is also set on satisfaction level and shared values of employees. Finally we describe applications which are important for managers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 381-389